Talfieq Al-Hadis (Studi Terhadap Hadis-Hadis Riwayat Imam Muslim Tentang Qunut) - Zainuddin, Zainuddin (PT. Sharia Journal and Education Center, 2025)
The diversity of information about qunut in the fifteen hadiths (numbers 294 – 308) contained in the Muslim version of al-Maktabah al-Syamilah refers to Abu Hurairah (three hadiths), Anas bin Malik (eight hadiths), Al-Barra bin 'Azib and Khufaf bin Ima (two hadiths each). Certainly, the emergence of contradictory meanings is inevitable as a consequence of this diversity. This is where talfieq al-hadith is needed to minimize or eliminate the meanings of the hadith that seem contradictory by finding a common point or combining their meanings. Based on this concept, the qunut informed by the Muslim Imam is inseparable from the incident in Bi'r Ma'unah the massacre of a group of believers in a very cunning manner this qunut is practiced in a series of obligatory prayers and lasts only one month with the substance of the prayer